Eğrisel Lamina Cam Kirişlerin Doğrusal Olmayan Davranışları - Dural, Ebru; Aşık, Mehmet Zülfii (Teorik ve Uygulamalı Mekanik Türk Milli Komitesi, 2010)
İn this study, a mathematical model is developed for the bending behavior of the laminated glass curved beams by minimizing the total potential energy of a laminated glass beam. The large deflection theory is used in the developing the model since the glass beams are very thin. The model is then validated by the experimental and finite element models for the simply and fıxed supported beams respectively. İt is presented that the behavior of laminated glass beams under large deflections could be linear or nonlinear regarding the boundary conditions or constraints.

Bu çalışmada bir lamina cam eğrisel kirişin tüm potansiyel enerjisinin en azlanması yolu ile lamina cam kirişlerin eğilme davranışı üzerine bir matematiksel model geliştirilmiştir. Modelin geliştirilmesinde lamina cam kirişler çok ince olduğundan büyük yerdeğiştirme kuramı kullanılmıştır. Ardından bu model deney yapılmak suretiyle ve sonlu elemanlar modelleri kullanılarak doğrulanmıştır. Büyük yer değiştirmelere maruz kalan lamina cam kirişlerin sınır şartlarına bağlı olarak doğrusal veya doğrusal olmayan davranış gösterebilecekleri sonucuna varılmıştır.

Conference Paper -- Theoretical and Applied Mechanical Turkish National Committee, 2010

Konferans Bildirisi -- Teorik ve Uygulamalı Mekanik Türk Milli Komitesi, 2010